Karl Schuhmann, Selected papers on phenomenology - Schuhmann, Karl. author. aut Link
XIII, 371 p.
Keywords: -Selected papers on phenomenology offers the best work in this field by the acclaimed historian of philosophy, Karl Schuhmann (1941-2003), displaying the extraordinary range and depth of his unique scholarship, -Topics covered include the development of Husserl's concept of intentionality, Husserl and Indian philosophy, the origins of speech act theory in Munich phenomenology, the historical background of the notion of "phenomenology", and Johannes Daubert's critique of Martin Heidegger, -This book brings together, in chronological arrangement, fourteen papers. Though thirteen of these were published before in some form, several were not easily accessible so far. In addition, a substantial piece of research, Schuhmann's chronicle of Johannes Daubert, appears here for the first time, -All articles have been edited in accordance with the author's wishes, and incorporate his later additions and corrections.